The polyphonic effect of intense accent in spoken discourse - Caldiz, Adriana (2011)
It is well known that the axiomatic belief that enunciation is attributable to only one voice has long been brought into question. Along these lines, Ducrot (1984) defines sense in terms of a multiplicity of 'voices' or 'points of view' expressed during the act of enunciating- voices that are enacted as an exchange, a dialogue or even a configuration of several simultaneous discursive characters. The studies carried out within the framework of the Linguistic Theory of Argumentation have demonstrated that the enunciation of full words and other words called 'tools' (connectors, operators, modifiers, etc.) reveals the manifestation of diverse argumentative viewpoints towards which the locutor adopts different attitudes. However, this polyphonic nature of language is not always exhibited in an evident and lexical or grammatical way. In spoken discourse other resources frequently prove relevant to the interpretation of meaning. In this work, we will analyse a prosodic feature that often makes the only ;signal marking the presence of a new enunciator and which simultaneously evinces a reaction on the part of the locutor, who, in turn, takes a stance with regard to such viewpoint. The study of the argumentative value of intonation1 is fairly recent. In previous works (García Negroni, 1995, 1998a, 2003, 2009), we have described the polyphonic instructions associated to an intense accent in speech. Along this line of thinking, this accent has been characterized as a constitutive mark of a type of modifier which we have called surrealisant. In a similar way, in our analysis of the enunciation of verbs (Caldiz 2007, 2008), we have been able to demonstrate how an emphatic prominence suggests the existence of a new point of view, attributable to an enunciator, which expresses a reversal of the polarity used by the locutor in his utterance. In this presentation we propose toaccount for the polyphonic instructions of intense accent (or intense prominence) and show how it manifests the viewpoints of virtual 'voices'. Intense accent is characterized by an emphatic prosody. Although this type of accent is not restricted to any particular genre, for this paper we have centred our analysis on academic discourse, which is fertile soil for the study of this intonational feature. This preliminary work is part of a wider project which seeks to demonstrate that, like words or phrases, certain prosodic features expose the polyphonic nature of sense and ;carry argumentative instructions. For this presentation we have analysed recordings from first undergraduate and graduate classes. The data, collected in different colleges, includes speakers of River Plate and Northern Peninsular Spanish. We have selected cases in which the polyphonic function of intonation unmistakably comes out as marked.